Perancangan User Experience Aplikasi Self-Checkout di Supermarket menggunakan Metode Human-Centered Design - Febby Anggara Putra; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Due to the Covid-19 pandemic, the government has implemented restrictions with various policies, one of which is social distancing. The implementation of this policy changes people's habits, including in shopping activities, which must now pay attention to the distance limits set by the government, while people must interact directly with other people, which is very high risk. This research aims to design a self-checkout application user experience in supermarkets to help overcome the limitation problem, so that people can do shopping activities without worrying if they have to interact with other people. Self-checkout is a facility that allows users to pay and pack their own groceries without the help of a cashier. This facility is very easy to use because users only need to scan shopping items, then pack and pay for them on the provided machine. Human centered design method is used in this research. This method has several stages, namely literature study, usage context analysis, user needs analysis, solution design design, solution design evaluation, result analysis and drawing conclusions. The design of this application produces visual designs in the form of wireframes, mockups, and prototypes. The test results with the help of Maze and Google Forms get an effectiveness aspect value of 94.29%, an efficiency aspect of 0.200 goals per second, and a user satisfaction aspect of 85.25 with an excelent adjective rating and grade A.